Isothermal cold crystallization kinetics of borassus powder/poly(lactic acid) biocomposites - Marathe, Yogesh Nana; Chellaswamy, Ramesh; Badiger, Manohar Virupax (Polymer Crystallization, 2020)
Poly(lactic acid) (PLA) is an important bioplastic which is semicrystalline with very slow crystallization rate. Therefore, the processed PLA products are usually amorphous and transparent with low mechanical properties. Currently, research efforts are focused on enhancing the crystallization rate of PLA. In this work, natural borassus fibers are incorporated into PLA and the isothermal cold crystallization kinetics is investigated using differential scanning calorimetry and Avrami equation. The isothermal cold crystallization studies revealed that, the relative crystallinity increases with the increasing content of borassus. The Avrami exponent “n” was determined ~2.0 indicated the one‐dimensional crystal growth with rod‐like geometry. The overall crystallization rate increased due to the borassus content and was expressed by crystallization halftime (t1/2). This study clearly showed that borassus fibers act as nucleating agent.

Investigation of domain structures in monomethoxy poly(ethylene glycol)-b-poly(caprolactone) grafted poly(acrylic acid) by NMR diffusion studies - Tiwari, Neha; Badiger, Manohar Virupax; Rajamohanan, Pattuparambil Ramanpillai; Ravindranathan, Sapna (Polymer International, 2022)
Associating polymers developed by grafting a block copolymer of monomethoxy poly(ethylene glycol)-b-poly(caprolactone) (MPEG-b-PCL) onto poly(acrylic acid) undergo an irreversible sol-gel transition on heating. The influence of various physicochemical parameters on the thermoresponsive behaviour was examined by rheology and NMR studies. Pulsed field gradient NMR diffusion studies were performed to probe the mechanism of thermally induced gelation. Analysis of the diffusion data reveals the presence of loosely and strongly associated structures which respond differently to variation in temperature. It is observed that the polymer solution, which is visibly homogeneous, is heterogeneous on a mesoscopic scale with a distribution of domains. Detailed investigation of the thermally induced sol-gel transition shows that the mechanism of gelation involves irreversible alterations in the domain structure and size. (c) 2022 Society of Industrial Chemistry.
Keywords: associating polymers; hydrophobically modified polymers; NMR diffusion studies; Rheology; sol-gel transition; thermoresponsive polymers